The transcription factor complex CmAP3-CmPI-CmUIF1 modulates carotenoid metabolism by directly regulating the carotenogenic gene CmCCD4a-2 in chrysanthemum. Issue 1 (19th February 2022) - Lu, Chenfei; Qu, Jiaping; Deng, Chengyan; Liu, Fangye; Zhang, Fan; Huang, He; Dai, Silan
Abstract: Carotenoids are one of the most important pigments for the coloring of many plants, fruits, and flowers. Recently, significant progress has been made in carotenoid metabolism. However, our specific understanding of the transcriptional regulation that controls the expression of carotenoid metabolic genes remains extremely limited. Anemone-type chrysanthemums, a special group of chrysanthemum cultivars, contain elongated disc florets in the capitulum that usually differ in color from the ray florets because of their different carotenoid contents. In this study, the carotenoid composition and content of ray and disc florets from the anemone-type chrysanthemum cultivar "Dong Li Fen Gui" were analyzed by high-performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS), and the key structural gene CmCCD4a-2, whose differential expression resulted in different carotenoid contents in these two types of florets, was identified. The promoter sequence of CmCCD4a-2 was then used as bait to screen a chrysanthemum flower cDNA library, and the transcription factors (TFs) CmAP3 and CmUIF1 were identified. Y2H, BiFC, and Y3H experiments demonstrated that these two TFs were connected by CmPI to form a CmAP3-CmPI-CmUIF1 TF complex. This TF complex regulated carotenoid metabolism by directly activating the expression of CmCCD4a-2 . A large number of target genes regulated directly by the CmAP3-CmPI-CmUIF1 TF complex, including carotenoid biosynthetic genes, flavonoid biosynthetic genes, and flower development-related genes, were identified by DNA-affinity purification sequencing (DAP-seq). This result indicated that the CmAP3-CmPI-CmUIF1 TF complex may participate in multiple processes. These findings expand our knowledge of the transcriptional regulation of carotenoid metabolism in plants and will be helpful for manipulating carotenoid accumulation in chrysanthemum.